Electrochemical detection of Toxocara canis excretory-secretory antigens in children from rural communities in Esmeraldas Province, Ecuador: association between active infection and high eosinophilia - Morales-Yánez, Francisco (Parasit Vectors, 2020)
BACKGROUND: The diagnosis of active Toxocara canis infections in humans is challenging. Larval stages of T. canis do not replicate in human tissues and disease may result from infection with a single T. canis larva. Recently, we developed a nanobody-based electrochemical magnetosensor assay with superior sensitivity to detect T. canis excretory-secretory (TES) antigens. Here, we evaluate the performance of the assay in children from an Ecuadorian birth cohort that followed children to five years of age. METHODS: Samples were selected based on the presence of peripheral blood eosinophilia and relative eosinophil counts. The samples were analyzed by the nanobody-based electrochemical magnetosensor assay, which utilizes a bivalent biotinylated nanobody as capturing agent on the surface of streptavidin pre-coated paramagnetic beads. Detection was performed by a different nanobody chemically labelled with horseradish peroxidase. RESULTS: Of 87 samples tested, 33 (38%) scored positive for TES antigen recognition by the electrochemical magnetosensor assay. The average concentration of TES antigen in serum was 2.1 ng/ml (SD = 1.1). The positive result in the electrochemical assay was associated with eosinophilia > 19% (P = 0.001). Parasitological data were available for 57 samples. There was no significant association between positivity by the electrochemical assay and the presence of other soil-transmitted helminth infections. CONCLUSIONS: Our nanobody-based electrochemical assay provides highly sensitive quantification of TES antigens in serum and has potential as a valuable tool for the diagnosis of active human toxocariasis. [Image: see text]